Historical Analysis of School Choice in Ontario: Freedom of Choice and Inequality - Glinos, Peter J. (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2021)
The article analyzes the contemporary school choice debate in Ontario in relation to the neoliberal models of education instituted by other provinces, and places key issues of the debate within Canada’s historical context. In the first section, this paper focuses on tracing out the push for neoliberal school choice in Ontario within the broader history of its development in Canada, with particular attention to Alberta and British Columbia. The second section examines two aspects of the school choice debate: the issues of freedom of choice, as well as racial and social inequality. Finally, these aspects of school choice are placed alongside Milton Friedman’s voucher school model and the history of education in Ontario. This juxtaposition reveals some of the regulations needed to mitigate the harmful effects of school choice in Ontario.